Tingkat Kesiapan Psikologi dalam Toilet Training Anak yang Memakai dan Tidak Memakai Disposable Diaper pada Usia 18-36 Bulan - Laviana Nita L; Dwi Setyorini; M Firman Ma'ruf (JURNAL ILKES : Jurnal Ilmu Kesehatan, 2018)
The habit of parents in disposable diaper will delay the child's time to start toilet training so that it can affect the readiness of children both physically and psychologically. The objective of this study is to analyze differences in the level of psychological readiness in toilet training children who wear and who do not wear disposable diaper at the age of 18-36 months. The design was descriptive comparative with cross sectional approach. The population was 66 respondents, with 40 respondents used purpossive sampling, that was collected using interviewes. The data analysis test used Mann-Whitney Test, p-value = 0,004 at significant level (α) = 0,05 then H1 accepted. It mean that there was difference of psychological readiness level in toilet training between children who worn disposable diaper and who did not at the age of 18-36 months with results showed that the group of children wearing disposable diaper who were most of the respondents (55%) had low level of psychological readiness in toilet training, while the children who did not wear it (70%) had been in the medium level of psychological readiness. Toilet training is influenced by the parent’s role such as parent’s job, parent’s understanding and knowledge of toilet training. Doing toilet training should be done immediately after the child shows signs that the child has been ready to start it, which can be a good habit to prevent the occurrence of death in persistent urinary system and psychological setbacks in children's toileting problems when they grow up.